Identificação de fatores de riscos cardiovasculares e o impacto da intervenção nutricional em trabalhadores da indústria na região metropolitana de Belém, Pará - (:unkn) unknown (Universidade Federal do Amazonas - Universidade Federal do Pará - Fundação Oswaldo Cruz, 2010)
This study aims to identify cardiovascular risk factors and the impact of nutritional intervention in the industrial sector workers in Greater Metropolitan Belém, Pará, companies accredited to the Workers' Food Program (WFP). We studied 97 employees of the Experimental group (ExpG) and 90 control group (GCON), were included in the randomization workers showed that cardiovascular risk factors for elevated waist circumference (WC). Participated in the randomization of 18 workers and 20 ExpG GCON. For the randomization tests, we used the paired Student t test and Wilcoxon test. Anthropometric variables were identified as Body Mass Index (BMI) and WC, blood levels of cholesterol, triglycerides and glucose levels and socioeconomic characteristics, and used the chi-square test for evaluating the results. The analysis of food consumption was made by means of food frequency questionnaire using a methodology based on the level of consumption: <0.33. Food consumption low,> 0.33 and <0.66 average consumption of food;> 0.66 Food consumption high. It was identified a young population, most living with a partner, with family incomes from 1 to 2 minimum wages, having completed high school. Before the dietary intervention was observed anthropometric findings with a high prevalence of overweight and high levels of lipid fractions in GExp and GCON. The consumption of foods considered cardiovascular risk was high when compared to consumption of foods considered protective in GExp and GCON. The characteristics found related to lifestyle were the improvement in the practice of smoking revealed a low percentage of smokers and former smokers, moderate, moderate to high alcohol consumption and low frequency of physical activity in both groups. After randomization the GCON showed only one variable with significant difference and there is a decrease in systolic blood pressure. In the analysis of anthropometric findings were observed high prevalence of overweight and high levels of lipid fractions in both groups before the intervention and significant improvement of nutritional values in the intervention group nutrition. In the experimental group, there was a significant difference in three variables: the average decrease in BMI, HDL cholesterol increased, demonstrating an apparent improvement after intervention and LDL cholesterol and a decrease of the mean, ie, demonstrating beneficial effects of the action guideline the group of workers ExpG. There was a decrease in CC ExpG signaling a decrease in an important risk factor for developing cardiovascular disease does so with GCON. The action of nutritional intervention results showed significant improvements for the group that was submitted when associated with the control group, confirming that the nutrition education strategy proposed in the TSP, it has practical effects of positive health worker.
Keywords: Fatores de riscos cardiovasculares - Trabalhadores; Impacto da intervenção nutricional - Trabalhadores; Cardiovascular risk factors; Impact of nutritional intervention; Programa de Alimentação do Trabalhador (PAT); OUTROS